2020
DOI: 10.1155/2020/5714546
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Mediation and Moderation Effect of Students’ Addiction to Virtual Reality Games: A Perspective of Structural Equation Modeling

Abstract: Virtual reality (VR) games construct an immersive context for the youth’s entertainment and learning. VR game addiction (VAD) occurs simultaneously and brings about psychological issues. The current research employed a maximum likelihood estimation method to construct a structural equation model, by which learners’ VR consumption behaviors were examined. The bootstrapping approach was adopted to explore further the mediation of VR realism (VRR) and the moderation of VR affordance on learners’ VAD, which potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 88 publications
1
5
0
Order By: Relevance
“…Addiction is sometimes called a desire; the high desire has a high probability of addiction towards anything he wishes for. Likewise, previous papers also support the stance of the current paper, which suggested that flow has a beneficial impact on the games' addiction behavior on the users [63]. Moreover, previous papers also suggest that besides the addiction, there are serious physical health concerns for those who use games excessively [64].…”
Section: Eoretical Implicationssupporting
confidence: 79%
“…Addiction is sometimes called a desire; the high desire has a high probability of addiction towards anything he wishes for. Likewise, previous papers also support the stance of the current paper, which suggested that flow has a beneficial impact on the games' addiction behavior on the users [63]. Moreover, previous papers also suggest that besides the addiction, there are serious physical health concerns for those who use games excessively [64].…”
Section: Eoretical Implicationssupporting
confidence: 79%
“…In this paper, we focus on the role of the social environment in Indonesian society that adopts a culture of collectivism in their lives to overcome the negative influence of globalization on adolescent premarital sexual behavior. In addition to having a positive (Zukhrufani and Zakiy, 2019;Amin, Hadisiwi and Suminar, 2022), recent research also shows the negative impact of the development of information technology on adolescent health and growth, such as virtual games and social media that can disturb the psychological state of adolescents (Zhai et al, 2020), depression (Revathi, Nair and Achuthan, 2020), headaches (Augner and Hacker, 2012) to increased behavior of premarital sex and sexual violence (Fairbairn, 2020). The unstoppable pace of globalization has a profound effect on social life.…”
Section: Theoretical Contributionmentioning
confidence: 99%
“…At present, academic research on negative behavior is mainly manifested as burnout behavior, dropout behavior, and even unsustainable use intention. Many scholars believe that the infuencing factors of negative behavior are primarily divided into internal and external dimensions, mainly internal factors based on information and content itself and external factors dominated by social pressure [41][42][43][44][45][46]. Information factors (such as ofensive content, ambiguity, advertising interference, and rampant rumors) of short video content are the main infuencing factors of burnout and negative behavior [41].…”
Section: User Behavior Research Related To the Short Video Appmentioning
confidence: 99%